La performance de exportación: Revisión teórica y propuesta de un marco integrador - F. Losada Pérez; Antonio Navarro García; E. Ruzo Sanmartín; J. M. Barreiro Fernández (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
The study of the factors that have an influence on firm's export performance is one of the more fruitful lines of research in international marketing literature. However, there is no agreement among the researchers about which ones are the determinants that have an influence on the results of firms' exporting activity. In this sense, starting from the main reviewing studies on this topic, the purpose of this work consists on proposing a conceptual model that contains the main variables that have an influence on the export performance.
Keywords: 330; export Performance; determinants; international